Two new species of the genus Pseudoliparis Finet (Orchidaceae, Malaxidinae) from New Guinea - Margońska, Hanna (Biodiversity: Research and Conservation, 2011)
Two new species of the genus Psudoliparis (Orchidaceae, Malaxidinae) from New Guinea are described, illustrated and its taxonomic affinity is briefly discussed. One new combination within the genus is proposed.